Hydrothermal reaction of cellulose in ionic liquid catalyzed by Er(OTf)3 - Tanawan Pinnarat; Nattajak Wongkam (My University, 2022)
This research explores the potential of ionic liquid to improve lactic acid yield of the hydrothermal reaction of cellulose. The research premise was that ionic liquid dissolved cellulose and water into liquid phase, which would facilitate the formation of glucose and lactic acid using water-tolerant catalyst Erbium (III) trifluoromethanesulfonate (Er(OTf)3). Contrary to the research premise, the experiment revealed that dissolving cellulose in ionic liquid prior to hydrothermal reaction lowered lactic acid yield while increasing hydroxymethylfurfural (HMF) yield. The phenomenon could be attributed to dissociation of water and ionic liquid to give hydronium ion and chloride ion, which subsequently formed hydrochloric acid (HCl). HCl catalyzed cellulose into HMF, in addition to lactic acid. Pressure and pressurized gas had minimal impact on the yield of lactic acid, while the hydrothermal reaction was affected by type of cation and anion of ionic liquid. The highest lactic acid yield of 54.26% was achieved by using 1-butyl-3 methylimidazolium chloride ionic liquid, with 190 °C, 30-min, 10 bar CO2 initial pressure, and Er(OTf)3 50 wt% cellulose. Meanwhile, the highest HMF yield of 66.06% was realized with 1-butyl-3-methylimidazolium hydrogen sulfate in the absence of Er(OTf)3.
Keywords: Advanced Cellulose Research Studies